Impact of chronic kidney disease on recurrent ventricular tachyarrhythmias in ICD recipients - Weidner, Kathrin; Behnes, Michael; Weiß, Christel; Nienaber, Christoph; Reiser, Linda; Kern-Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Rusnak, Jonas; Schupp, Tobias; et al. (Heart and vessels, 2019)
The study sought to assess the impact of chronic kidney disease (CKD) on recurrences of ventricular tachyarrhythmias in implantable cardioverter defibrillator (ICD) recipients. Data regarding the outcome of patients with CKD in ICD recipients is limited. A large retrospective registry was used including consecutive ICD recipients surviving episodes of ventricular tachycardia (VT) or fibrillation (VF) from 2002 to 2016. CKD patients were compared to non-CKD patients. The primary endpoint was the first recurrence of ventricular tachyarrhythmias at 5 years. Secondary endpoints were ICD-related therapies, rehospitalization and all-cause mortality at 5 years. Kaplan-Meier, multivariable Cox regression and propensity score matching were applied. A total of 585 consecutive patients were included (non-CKD: 57%, CKD: 43%). CKD had higher rates of the primary endpoint of recurrent ventricular tachyarrhythmias compared to non-CKD patients (50% vs. 40%; log rank p = 0.008; HR = 1.398; 95% CI 1.087-1.770; p = 0.009), which was irrespective of a primary or secondary preventive ICD and mainly attributed to recurrent VF (11% vs. 5%; p = 0.007) and electrical storm (ES) (10% vs. 5%; p = 0.010). Accordingly, CKD patients had higher rates of the secondary endpoint of appropriate ICD therapies (41% vs. 30%; log rank p = 0.002; HR = 1.532; 95% CI 1.163-2.018; p = 0.002), mainly attributed to appropriate ICD shocks (19% vs. 11%; p = 0.005). After multivariable Cox regression CKD was associated with a 1.4-fold higher risk of appropriate device therapies (HR = 1.353; 95% CI 1.001-1.825; p = 0.049), but not with first recurrence of ventricular tachyarrhythmias (p = 0.177). Irrespective of propensity score matching, CKD was associated with increasing all-cause mortality at 5 years (p = 0.001). The presence of CKD is associated with increased rates of recurrent ventricular tachyarrhythmias, appropriate device therapies, mainly attributed to appropriate shock, and all-cause mortality in ICD recipients at 5 years.
Gesehen am 07.02.2020